A case of gastric cancer metastasis to the breast in a female with BRCA2 germline mutation and literature review. Issue 1 (2nd January 2019) - Dulskas, Audrius; Al Bandar, Mahdi; Choi, Yoon Young; Shin, Su-Jin; Beom, Seung-Hoon; Son, Taeil; Kim, Hyung-Il; Cheong, Jae-Ho; Hyung, Woo Jin; Noh, Sung Hoon
Abstract: Introduction: Gastric cancer is a deadly disease. Common sites of distant metastasis of gastric cancer are the peritoneum, liver, lymph nodes, and lung. The breast is a rare site of metastasis in gastric cancer which occurs in males dominantly. Patients and methods: Here, we report the first case of metastatic gastric cancer to the breast in a patient with the breast cancer 2 ( BRCA2) germline mutation. A 34-year-old female was admitted to the hospital with dyspepsia and a palpable mass in the left breast. Gastric cancer was confirmed to be signet ring cell adenocarcinoma. The breast mass exhibited histological properties consistent with gastric cancer. Immunohistochemistry results showed the breast tumor was CDX-2 and CK20-positive, but ER-, CK7-, and GATA3-negative. The BRCA1 gene had a wild-type sequence, but a heterozygous variant was discovered in BRCA2 in exon 10 (c.1744A > C, p.T582P); the significance of this variant is unknown. Results: The patient received palliative XELOX (capecitabine + oxaliplatin) with radiation therapy to the stomach. The breast tumor resolved completely, but the overall response was partial. Conclusion: Gastric cancer metastasis to the breast is rare, but should be considered in young female patients with signet ring cell type gastric cancer.